Influence of carbohydrate supplementation on plasma cytokine and neutrophil degranulation responses to high intensity intermittent exercise - Bishop, N. C.; Gleeson, M.; Nicholas, C. W.; Ali, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
Ingesting carbohydrate (CHO) beverages during prolonged, continuous heavy exercise results in smaller changes in the plasma concentrations of several cytokines and attenuates a decline in neutrophil function. In contrast, ingesting CHO during prolonged intermittent exercise appears to have negligible influence on these responses, probably due to the overall moderate intensity of these intermittent exercise protocols. Therefore, we examined the effect of CHO ingestion on plasma interleukin-6 (IL-6), tumor necrosis factor-a (TNF-a) and lipopolysaccharide (LPS)-stimulated neutrophil degranulation responses to high-intensity intermittent running. Six trained male soccer players performed 2 exercise trials, 7 days apart, in a randomized, counterbalanced design. On each occasion, they completed six 15-min periods of intermittent running consisting of maximal sprinting interspersed with less intense periods of running and walking. Subjects consumed either CHO or artificially sweetened placebo (PLA) beverages immediately before and at 15-min intervals during the exercise. At 30 min post-exercise, CHO versus PLA was associated with a higher plasma glucose concentration (p < .01), a lower plasma cortisol and IL-6 concentration (p < .02), and fewer numbers of circulating neutrophils (p < .05). Following the exercise, LPS-stimulated elastase release per neutrophil fell 31% below baseline values on the PLA trial (p = .06) compared with 17% on the CHO trial (p = .30). Plasma TNF-a concentration increased following the exercise (main effect of time, p < .001) but was not affected by CHO. These data indicate that CHO ingestion attenuates changes in plasma IL-6 concentration, neutrophil trafficking, and LPS-stimulated neutrophil degranulation in response to intermittent exercise that involves bouts of very high intensity exercise.